ANALISIS PENGARUH INVESTASI TEKNOLOGI INFORMASI DALAM BIDANG E- COMMERCE (STUDI KASUS PT MATAHARI DEPARTMENT STORE TBK) - Ni Made Estiyanti; Ni Kadek Adi Istriawati; I Putu Satwika (Politeknik Negeri Jakarta, 2021)
E-commerceis one of the times and Information Technology (IT) that trades using the internet or what is called online sales. The impact of e-commerce on PT. Matahari Department Store Tbk, which invests in e-commerce in developing its business. Therefore it is necessary to know the effect of e-commerce on companies and the importance of analyzing an investment, whether it is feasible or not to be developed and implemented in a company. The method used in this research is a qualitative descriptive approach, a comparative analysis method of financial statements and a method of cost benefit analysis (CBA). The results of research on the impact of e-commerce on companies are investing in IT in the field of e-commerce, developing the concept of omni-channel, conductingrebranding site to Matahari.com, decreased stocks, decreased profits, increased liabilities, while total assets and equity decreased in 2018 due to decreased profits, and the results of calculations on the benefits and costs of investing in e-commerce had a positive effect on ROI, NPV, PP, BCR, so this investment can be accepted. Keywords: E-commerce, Comparative Analysis of Financial Statements, Investment, Information Technology, Cost Benefit Analysis